PENCIPTAAN NARASI PRODUK BUDAYA MASYARAKAT DESA PLUNTURAN KECAMATAN PULUNG KABUPATEN PONOROGO - Y.B. Agung Prasaja; Edy Wahyudi (Universitas 17 Agustus 1945 Surabaya, 2020)
ABSTRACT Narrative can grow and develop regardless of geographical background. Of the various definitions of narrative, most of them relate the two main characteristics of it, namely: 1) events, governed by temporality-chronology of events and their presentation in the text; 2) telling or making a story, as a verbal act of mediation. Narrative is used to accommodate the interests of society such as ideology, nationalism, social relations, cultural order. These aspects include natural aspects, geographical aspects, social aspects, cultural aspects, political aspects, historical aspects, philosophical aspects, anthropological aspects, economic aspects, language aspects, artistic aspects, mythological aspects, technological aspects. Research on the ethnographic aspects of the people of plunturan village seeks to reveal the problems formulated as follows; 1. How is the construction of cultural products built by the villagers of plunturan, pulung district, kab. Ponorogo. 2. How the narrative was created by the villagers of Plunturan Pulung, Ponorogo? The phenomenon of narrative, literary works, art works, and cultural products are entities that are interrelated with one another, this also occurs in the community of plunturan village. Ethnography is defined as a form of investigation that relies heavily on participant observation, at least researchers are in a marginal position, trying to document in detail, patterns of interaction, people's perspectives, and patterns of their daily understanding and manifest the imagination of the people of plunturan kec. Pulung kab ponorogo in narrative form. Keywords: ethnography, narrative, culture, local, interdisciplinary